Analisis Kepercayaan Guru SMP Swasta di Kabupaten Tangerang - Syafa’at Ariful Huda; Muhamad Suhardi; Nurimani Nurimani; Yatha Yuni (Universitas Pendidikan Mandalika (UNDIKMA), 2020)
The purpose of this study is to analyze the effect of organizational justice on the trust of Tangerang Regency private junior high school teachers. In the analysis will get more detailed results related to organizational justice variables with the indicators and trust with the indicators. This research used SEM (Structural Equition Model) method. Data collection technique used a questionnaire. The sample of this study involved 273 people through random proportional selection. Data were analyzed using descriptive statistics and structural equation modeling in inferential statistics. The results of this study indicate that there was a direct effect of organizational justice on the confidence of Tangerang regency private junior high school teachers. The dominant indicators of organizational justice variables which contributed was neutrality at 18.26%, while the dominant trust variable which contributed was consistency at 23.71%.